PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP NIAT BELI ULANG (Studi kasus pada Toko OB. Second Cirebon) - Muhammad Fauzan; Pebi Kurniawan; Ali Jufri (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the influence of service quality and store atmosphere on customers' repurchase intention at OB.Second thrift store in Cirebon. In the rapidly growing digital era, where fashion trends change quickly, aesthetic aspects and shopping experience are key factors in the decision to repurchase. This study examines the effects of service quality and store atmosphere on repurchase intention using the Theory of Planned Behavior, Expectation Confirmation Theory, and Stimulus-Organism-Response (SOR) Model. Direct observation and a quantitative approach using questionnaires are the research methods used. The results show that repurchase intention is positively and significantly impacted by both store atmosphere and service quality. Improving customer satisfaction and creating a cozier retail environment can boost repeat business and future sales.